ANALISIS FAKTOR-FAKTOR YANG MENENTUKAN MINAT MIGRASI PENDUDUK SIRKULER KE KOTA SUMBAWA - Abdul Rahim; Ika Fitriyani; Riska Septia Ningrum (Pusat Riset dan Publikasi, 2022)
This study aims to know the factors that determine the interest in circular migration of the population to the city of Sumbawa. These factors include age, income, occupation, education level, marital status and land ownership. Type of this study was associative. The type of data used in this study was quantitative data. The data used in this study were primary that obtained directly from its source through questionnaires and secondary data were collected through documentation. Data analysis were used multiple linear regression analysis techniques, t and F statistical tests and the coefficient of determination (R2). To do data analysis was done through application of SPSS version 16.0 for windows application. The results showed that income and occupation variables had a significant effect on interest in circular migration of the population to the city of Sumbawa, while the variables of age, education level, marital status and land ownership had no effect on circular migration interest of the population to the city of Sumbawa. Simultaneously, the variables of age, income, occupation, education level, marital status and land ownership have a significant effect on the interest in circular migration of the population to the city of Sumbawa. The ability of the variables of age, income, occupation, education level, marital status and land ownership to influencing the variation of changes the interest in circular migration of the population to the city of Sumbawa was 95.9%, while the remaining of 4.1% was influenced by other variables outside the model research.